Microsoft SQL server 2008 : T-SQL fundamentals - Ben-Gan, Itzik (Redmond, Wash. : Microsoft Press, 2009)
"Master the foundations of T-SQL with the right balance of conceptual and practical content. Get hands-on guidance - including exercises and code samples - that show you how to develop code to query and modify data. You'll gain a solid understanding of the T-SQL language and good programming practices, and learn to write more efficient and powerful queries." --Book Jacket
Keywords: SQL server; SQL (Computer program language); Client/server computing